غلامی کے خاتمے میں اسلام اور مسلمانوں کا کردار : Role of Islam and Muslims in Eradicating Slavery - Dr, Amjad Hayat; Dr, Rizwan Haider (jihat-ul-islam, 2023)
The concept of slavery in Islam has garnered attention since the abolition of slavery in the past century. Although often briefly discussed, a comprehensive understanding necessitates examining slavery from both economic and religious standpoints. However, adversaries of Islam have seized opportunities to raise objections, claiming that Islamic texts endorse slavery. Concurrently, the rise of extremist groups such as ISIS and Boko Haram has witnessed the resurgence of slavery, flouting international agreements. The current state of affairs calls for a clarification of the Islamic perspective on slavery, emphasizing Islam's foundation of human equality and its measures to eradicate slavery. Notably, Al-Mami Abdul Qadir Khan holds the distinction of being the first ruler to abolish slavery at the state level in Senegambia, highlighting Muslim contributions in this endeavor. In light of these developments, it is crucial to address misconceptions and promote a holistic understanding of Islam's stance on slavery, fostering a world free from the shackles of oppression.